Metal-oxide inhalation induced fever - Immuntoxicological aspects of welding fumes - Szűcs-Somlyó, Éva; Lehel, József; Májlinger, Kornél; Lőrincz, Márta; Kővágó, Csaba (Food and chemical toxicology, 2023)
Metal fume fever is a well-known occupational disease that arises from prolonged exposure to subtoxic levels of zinc oxide-containing fumes or dust. This review article aims to identify and examine the possible immunotoxicological effects of inhaled zinc oxide nanoparticles. The current most widely accepted pathomechanism for the development of the disease involves the formation of reactive oxygen species following the entry of zinc oxide particles into the alveolus resulting the release of pro-inflammatory cytokines by activation of the Nuclear Factor Kappa B transcriptional signal, thus evoking the symptoms. The role of metallothionein in inducing tolerance is believed to be a key factor in mitigating the development of metal fume fever. The other, poorly proven hypothetical route is that zinc-oxide particles bind to an undefined protein in the body as haptens to form an antigen and act as an allergen. After activation of the immune system, primary antibodies and immune complexes are developed and type 1. hypersensitivity reaction occurs, that can cause asthmatic dyspnoea, urticaria and angioedema. The development of tolerance is explained by the formation of secondary antibodies against primary antibodies. Oxidative stress and immunological processes cannot be completely separated from each other, as they can induce each other. •Metal fume fever usually arises from prolonged exposure to subtoxic levels of zinc oxide-containing fumes or dust.•Although several studies have investigated the pathomechanism of the disease, it remains unclear.•The most widely accepted pathomechanism is the formation of ROS, which activate the NFκB pathway.•Alternatively, ZnO particles may cause inflammation directly or act as haptens and trigger a hypersensitivity reaction.